Pengaruh Persepsi Usaha, Literasi Keuangan, Pengetahuan Akuntansi Dan Pengalaman Usaha Terhadap Perilaku Keuangan UMKM (Studi Kasus Di Glugur Kota Medan) - Kevin Tjanriadi Harun; Arie Pratania Putri; Evelyn Evelyn; Alistraja Dison Silalahi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Medan city as the capital of North Sumatra province is the largest city in the eastern region of Sumatra island. Micro, Small and medium enterprises, often called UMKM, are forms of business managed by a person or group of people with a certain amount of capital and set up a business with the aim of making a profit with the ability to develop flexible business processes. The approach in this study is a quantitative approach. In this study, researchers used quantitative descriptive research methods. Total population and sample of 63 business units. Data collection techniques are questionnaires, interviews and documentation. Data analysis techniques using E-view. The conclusion of this study is that the perception of business has a positive and significant effect on the financial behavior of UMKM, Financial Literacy, accounting knowledge and business experience do not affect the financial behavior of UMKM. Implementation of business perception, financial literacy, knowledge and business experience support can encourage high financial behavior. Keywords: Business Perception, Financial Literacy, Accounting Knowledge, Business Experience Financial Behavior